Quality Analysis Of Jelly Candy Produced From Different Drying Techniques - Ayni, Resti Aswatul; Holinesti, Rahmi (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
Jelly candy is a intermediate moisture product. The jelly candy is usually dried by using sunshine, but if the weather is overcast event it rains the drying process can not be done. Therefore, the drying process can be done by using mechanical tool, namely food dehydrator. The use of a food dehydrator is one of the alternative that can be used for drying. The purpose of this research is to analyze the quality of jelly candies produced from sun drying techniques and food dehydrator with organoleptic test on the quality of shape, color, scent, texture, and taste of jelly candy. This type of research is a true experiment using a Rancangan Acak Lengkap (RAL) with two treatments and three repetitions. Techniques of data collection is questionnaire for four expert panelist, some lectures from Ilmu Kesejahteraan Keluarga concentration Tata Boga Universitas Negeri Padang with primary data. Data is tabulated with level test and continued with analyze using the t-test. The best result can be found on the treatment by using food dehydrator (X2) due to the temperature on the tool can be set, thus the drying process become stable and controllable.